2021
DOI: 10.11604/pamj.2021.38.336.28953
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination hesitancy among women of reproductive age in resource-challenged settings: a cause for public health concern

Abstract: Women of reproductive age are a key population for the control of COVID-19 owing to their levels of socio-economic activities and central role in the upkeep of stable families. Therefore, adequate vaccination uptake in this population is critical. However, this may be negatively affected by circulating rumours regarding SARS-CoV-2 vaccines and subfertility and pregnancy and breastfeeding concerns that have circulated widely on diverse social media. Urgent public health interventions are required to deal with v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 10 publications
0
24
0
Order By: Relevance
“…Previous studies have reported several factors that may explain the populations’ hesitancy in COVID-19 vaccine acceptance. The factors include lower economic level [ 43 ], concerns about the possibly damaging outcome of the COVID-19 vaccines to developing babies in the womb [ 44 ], conspiracy beliefs regarding the COVID-19 vaccine might cause infertility and miscarriages [ 45 ], and less perceived susceptibility [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported several factors that may explain the populations’ hesitancy in COVID-19 vaccine acceptance. The factors include lower economic level [ 43 ], concerns about the possibly damaging outcome of the COVID-19 vaccines to developing babies in the womb [ 44 ], conspiracy beliefs regarding the COVID-19 vaccine might cause infertility and miscarriages [ 45 ], and less perceived susceptibility [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…As complications, hospitalization, and mortality from the COVID-19 viral infection are found to be less severe for younger populations [ 34 , 35 ], the need for vaccination may not be sufficiently emphasized. Vaccine hesitancy among younger women may be related to additional concerns about reproductive health and breastfeeding [ 11 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Second, the safety of the vaccine may also be relevant. Previous studies have provided evidence of concerns regarding vaccine safety and side effects among reproductive-age women [ 11 , 36 , 37 ]. Younger women with lower confidence in their health may be more concerned about possible side effects and may be hesitant to be vaccinated.…”
Section: Discussionmentioning
confidence: 99%
“…This study found that women were more hesitant than men regarding receiving the COVID-19 vaccination, which is supported by the findings of other studies [23,24]. The low economic ability of women [25], women’s concerns regarding the potentially harmful effect of the COVID-19 vaccines towards developing baby in the womb, and young children [26], conspiracy beliefs among women regarding COVID-19 vaccine imposed subfertility, infertility, and miscarriages [27], and less perceived susceptibility regarding contracting Coronavirus among women [28] are playing a role towards constructing increased vaccine hesitancy among the women.…”
Section: Discussionmentioning
confidence: 65%